Debts of despair: Education, financial losses, and precursors of deaths of despair - Samuel H. Fishman; Iliya Gutin (Elsevier, 2021)
Recent deaths of despair literature hypothesizes that financial losses are a key mechanism through which education is associated with higher risk for drug use, alcohol abuse, and suicidal ideation. However, few studies have empirically assessed the significance of this harmful pathway or compared it to other hypothesized explanations. Drawing on data from over 8000 respondents in the National Longitudinal Study of Adolescent to Adult Health, this paper finds that lower education-levels are associated with heightened risk of drug use, painkiller use, frequent binge drinking, and suicidal ideation; in turn, decompositions reveal that financial losses mediate about 20 percent of the association between education with drug use and suicidal ideation. The results support a core assumption of the deaths of despair hypothesis-that financial losses among those with low education-levels drive the increase in harmful despair-associated behaviors, which often precede disease and mortality. Future research should extend this work by linking individual-level socioeconomic and health patterns with broader economic changes to better understand how individuals' educational attainment interacts with macro-level structural factors to shape their vulnerability to despair-associated disease and death.